Penataan Ruang Pameran Seni Lintas Batas - Mahendra, I Komang Aditya; Sujana, I Wayan; Jodog, I Made (Program Studi Seni Murni ISI Bali, 2023)
The arrangement of an exhibition space is the main focus raised in the writing of this thesis with the title